2014
DOI: 10.2528/pierl14072203
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Dual-Band Printed Monopole Antenna for Wimax/Wlan Applications

Abstract: Abstract-A compact printed dual-band antenna for WiMAX/WLAN applications is proposed in this paper. The dual-band monopole antenna consists of a triangular patch and two folding arms shorted to the ground plane. The proposed antenna features a low profile and compact dimension. To avoid via process in the fabrication, the triangular patch and two folding arms are separately constructed on the two sides of a FR4 substrate. By employing this structure, five different resonances can be yielded. The triangular pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Some studies used slot structure to achieve a multi-band resonance with a compact antenna size [1][2][3]. Also, some other promising structures have been proposed, such as monopole [4,5], CPW-fed [6,7], ACS [8, 9] and PIFA [10]. In [2], An instance is shown that a printed planar antenna with a size of 30 × 30mm 2 generated three resonant modes by two dissimilar inverted L-shaped slots and a mushroom-shaped slot loaded into the antenna.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies used slot structure to achieve a multi-band resonance with a compact antenna size [1][2][3]. Also, some other promising structures have been proposed, such as monopole [4,5], CPW-fed [6,7], ACS [8, 9] and PIFA [10]. In [2], An instance is shown that a printed planar antenna with a size of 30 × 30mm 2 generated three resonant modes by two dissimilar inverted L-shaped slots and a mushroom-shaped slot loaded into the antenna.…”
Section: Introductionmentioning
confidence: 99%
“…In [2], An instance is shown that a printed planar antenna with a size of 30 × 30mm 2 generated three resonant modes by two dissimilar inverted L-shaped slots and a mushroom-shaped slot loaded into the antenna. In [4], a compact microstrip-fed dual-band monopole with size of 10 × 30mm 2 was presented to cover WiMAX and WLAN bands by a triangular monopole and two folding arms shorted to the ground plane. In [9], a ACS structure antenna with a size of 28 × 28mm 2 used a folding microstrip line radiator along with unilateral ground plane to generate four desired frequency bands, while the bandwidth of each band is rather limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [2], An instance is shown that a printed planar antenna with a size of 30 × 30mm2 generated three resonant modes by two dissimilar inverted L-shaped slots and a mushroom-shaped slot loaded into the antenna. Also, some other promising structures have been proposed, such as monopole [4,5]. In the diversity aspect, some efforts are made to enhance the diversity performance and reduce the volume.…”
Section: Introductionmentioning
confidence: 99%
“…However, the restrict space limitation in the mobile handset devices design increases the difficulties of multi-band antenna toward compact, low profile and board bandwidth for the devices. Therefore, a deals of research and approach has been achieving to increase bandwidth and reduce the antenna volume [1][2][3][4][5]. Slot structure was used to achieve a multi-band resonance with a small size in some studies [1][2][3].…”
Section: Introductionmentioning
confidence: 99%